THE INFLUENCES OF INTEREST RATE AND INFLATION ON SHARIA MUTUAL FUND PERFORMANCE - Achmad Fauzi (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
ABSTRACT This research aims to determine the significance of the influence of interest rate and inflation on the performance of sharia mutual funds. This research was conducted on sharia mutual fund-type shares listed with the Financial Services Authority (Indonesia) (OJK) for the 60 months observed. Sharpe’s method was used for measuring the performance of the mutual funds used. This study uses a secondary quantitative research approach and the analysis technique used is multiple linear regression. Based on the result of the t test, interest rate is shown to have a significant negative effect on the performance of sharia mutual funds while inflation does not have a significant effect on their performance. Keywords: Interest rate, BI rate, inflation, performance of mutual fund, Sharpe’s method.